New Model of Inclusive Higher Education Practices in Megacities’ Universities - Lantsova, Irina; Kutsuri, Georgiy; Shcherbatykh, Lyudmila; Gladysheva, Marina; Grebennikova, Veronica; Morán, Próspero; Kosov, Mikhail; Singer, Nermeen; Muda, Iskandar; Dudnik, Olesya (Emerging Science Journal, 2024)
This study analyzes the problem of higher professional education for people with disabilities in multinational megacities from different countries. The aim of this paper is to investigate the emerging changes and perspectives of educational inclusion in the universities of Moscow, Jakarta, Barcelona, and Cairo and to develop a new model of inclusive educational practice for universities based on an inclusive ideology of understanding the position of people with disabilities in the education system and society overall. To perform this study and verify the new model proposed by the authors, participants were selected from ten universities that indicated parameters such as accessibility, participation, quality, students’ education results, and government funding. The survey aimed to collect participants’ perspectives and experiences from diverse elements of the higher education community in the aforementioned locations. 751 participants were selected for the survey with a balanced gender distribution: 48.6% men and 51.4% women. Age distribution was rather diverse: the age group of 18–24 years was 25,7%, the age group of 25–34 years was 27,3%, the age group of 35–44 years was 25,6%, and the age group of 45 years 21,4%. Another distribution was people without disabilities (N=250) and with disabilities (N=551). The reliability of the research was achieved using several methods, including ANOVA. The results of this research show similarities and differences in implementing inclusive education practices across selected locations, providing a detailed picture of the current state and future perspectives of higher inclusive education. The scientific novelty of this research lies in the theoretical-methodological rationale of the new model of inclusive higher education practices in universities of major megacities and in forming the propositions on this model’s implementation in higher education institutions. Doi: 10.28991/ESJ-2024-SIED1-03 Full Text: PDF